Investigation of methylation status of interleukin-16 and autoimmune regulator gene promoter regions in Behçet's disease - Melih Akpunar,; Demet Yalcin Kehribar,; Serkan Günaydın,; Hilal Koyuncu,; Zülfinaz Betül Celik,; Metin Özgen, (Archives of Rheumatology, 2025)
Objectives: The aim of this study was to determine the epigenetic changes in interleukin-16 (IL-16) and autoimmune regulator (AIRE) genes in Behçet’s disease (BD) and to investigate the relationship between these changes and the disease mechanism. Patients and methods: Between October 2022 and January 2023, a total of 40 patients (20 males, 20 females; mean age: 37.0±11.4 years; range, 19 to 71 years) who met the 2014 International Criteria for Behçet’s Disease with no concomitant diseases and who were either newly diagnosed or under follow-up and 40 age- and sex-matched healthy hospital staff as the control group (20 males, 20 females mean age: 35.1±5.7 years; range, 29 to 45 years) with no chronic diseases or active infections were included. Peripheral blood samples were obtained from all participants, and genomic deoxyribonucleic acid (DNA) was isolated. The DNA samples were modified using a bisulfite modification kit. Subsequently, the promoter methylation profiles of IL-16 and AIRE genes were determined using methylation-specific polymerase chain reaction (MSP) with primers specifically designed for methylation. Results: In both BD and control groups, methylation was detected in the promoter region of IL-16, indicating a weak expression of the IL-16 gene. In contrast, while the promoter region of the AIRE gene was methylated in all control participants, it was unmethylated in all patients with BD. Conclusion: This is the first study to evaluate the methylation status of both AIRE and IL-16 genes in BD. Our study results suggest that the promoter region of the AIRE gene is unmethylated in BD and that AIRE gene is activated in BD and produces autoimmune regulatory proteins that eliminate autoreactive T cells, suggesting a tendency toward autoimmunity in BD. These findings also suggest that IL-16, which is involved in the pathogenesis of many rheumatic diseases, does not play a significant role in the pathogenesis of BD.